Aspectos cognitivos de autores de violência sexual contra crianças e adolescentes - Perissinotto, Rodrigo (2019)
The present dissertation is organized in two articles, which aim to evaluate the cognitive aspects of the sex offenders (SO) against children and adolescents, discussing differences according to the presence or not of psychopathy. The first article, a correlational study, aims to evaluate the cognitive aspects of SO through the Rorschach Performance Assessment System (R-PAS) and its comparison with the adult reference data in the test. 70 incarcerated sex offenders against children and adolescents participated in this study. The instruments used were a Protocol for Collecting Information in Criminal Proceedings; the Rorschach test (R-PAS) considering the variables of the domains Engagement and cognitive processing and Problems of thought and perception. Data analysis was performed using Student's t-test for a sample, comparing SO results with the means available in the normative tables of the test manual. The results corroborate with studies that point to cognitive impairments in SO. More specifically, SO have revealed more simplistic involvement and cognitive processing, with few efficient resources available for involvement in stressful situations, as well as disturbances in perception and thought. The second article had as objective to discuss the cognitive differences, as evaluated by the R-PAS, between SO according to the presence or not of psychopathy. In addition, we sought to understand whether cognitive aspects can explain the variance of the psychopathy construct. Thirty voluntary SO (10 psychopaths, 20 non-psychopathic) participated in the study, serving a closed sentence in a penitentiary. The instruments used were: a Protocol for Collecting Information in Criminal Proceedings; the Psychopathy Checklist-Revised (PCL-R) to characterize psychopathy; the Rorschach test (R-PAS) considering the variables of the domains Engagement and cognitive processing and Problems of thought and perception. Data analyzes used Student's t, Cohen's d effect size and regression analyzes. In the comparison between groups, it was observed that the group of participants with psychopathy presented disorganization of the thought, as well as greater vulnerability to the general disorganization of the personality. The best regression model identified that 55% of psychopathy can be explained by a higher propensity for general personality maladjustment as assessed by R-PAS variable EII-3, associated with a predisposition to be arrested younger. The results found in both studies suggest that cognitive deficits constitute vulnerabilities for the development of disorders associated with crime and also sexual violence.